Phase separation in RbxFe2−ySe2probed by non-stoichiometry and cu doping - Shylin, Sergii I.; Ksenofontov, Vadim; Medvedev, Sergey A.; Tsurkan, Vladimir; Felser, Claudia (Journal of Superconductivity and Novel Magnetism, 2015)
The paper presents Mössbauer spectroscopy investigation on superconducting Rb0.8Fe1.6Se2 exhibiting nanoscale phase separation and two its derivatives: Cu-doped Rb0.8Fe1.56Cu0.04Se2and Fe-deficient Rb0.7Fe1.4Se2. The spectra reveal the presence of the same dominant magnetic sextet in the samples, which is assigned to the Fe 16i sites of the √ 5 × √ 5 × 1 superstructure. This magnetic part is independent on the modification of the sample and does not undergo any changes after doping or deviation of stoichiometry. In contrast, the minor non-magnetic doublet in the spectra of Rb0.8Fe1.6Se2, which is attributed to the superconducting nanoscale phase, is sensitive to such modifications. After doping with Cu, the relative intensity of non-magnetic doublet significantly decreases together with suppression of superconductivity. On the other hand, the Fe-deficient sample is entirely magnetically ordered below 250 K including in the minor nanoscale phase. A discussion of Mössbauer spectroscopic data and comparison with previous studies on other Fe chalcogenide analogues allow to conclude the nanosized phase separation is also observed in non-stoichiometric and doped modifications of Rb0.8Fe1.6Se2.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cu doping; Mössbauer spectroscopy; Phase separation; Rb